Influences of linearly polarized light and linearly polarized vectors on the visual selection sensitivity and polartactic response effect of locusts - Liu, Qihang; Yang, Bo; Hou, Yimin; Kong, Yifan; Zhang, Pingchuan; Cui, Jianxin (International Journal of Agricultural and Biological Engineering, 2025)
To clarify the function effect of spectrum and linear polarization-coupled light on locusts’ induction, determine the influence factors of linearly polarized light on locusts’ polartactic characteristics, construct the technical characteristics of locusts’ polarization induction, and develop locusts’ polartactic induction photo-source, this study investigated the functional influence of spectral light and linear polarization-coupled light on locust phototactic and polartactic behavior. A linearly polarized light source system was used to determine the polartactic response of locusts induced by different linearly polarized vectors under normal light conditions. The results demonstrated that, within the context of spectral and linear polarization-coupled light, the visual response sensitivity of locusts was related to the spectral light intensity, being highest in response to orange light intensity. The visual aggregation and selective sensitivities of locusts were both influenced by spectral irradiation distance, with the violet spectrum inducing the strongest sensitivity in both cases. The polartactic chord function tuning response characteristics at different angles (0°-360°) were associated with linear polarization spectrum attributes. The polartactic response of locusts was related to changes in visual sensitivity resulting from the distance from the linear polarization light source, being optimal in response to the orange spectrum, whereas the violet spectrum induced the optimal visual and polartactic aggregation sensitivities. Furthermore, the specificity of chord function tuning response characteristics with periodic vector variations in a heterogeneous spectrum showed significant changes. An orange spectrum vector mode led to the most pronounced changes in response, whereas the violet spectrum vector mode exhibited the most significant changes in chord function properties. These variations in chord function and period induced by spectrum impacted the functional effect of linear polarization vector modes and reset the sensitive vector of locust polarization vision. Specifically, under the orange spectrum, locusts exhibited the highest polartactic response sensitivity at 330° vector, whereas, under the violet spectrum, the polartactic aggregation sensitivity was most pronounced at 30° vector, and visual trend sensitivity was optimal at 120° vector. Our results provide theoretical support for the study of the specific sensitivity nature of locust phototactic and polartactic behaviors, and the construction of a mechanism for inducing the polarization spectrum in locusts. Key words: Locusta migratoria; linearly polarized light; linearly polarized vectors; visual selection sensitivity; polartactic response effectDOI: 10.25165/j.ijabe.20251802.9002Liu Q H, Yang B, Hou Y M, Kong Y F, Zhang P C, Cui J X. Influences of linearly polarized light and linearly polarized vectors on the visual selection sensitivity and polartactic response effect of locusts. Int J Agric & Biol Eng, 2025;18(2): 27–34.